On scalar-type spectral operators and Carleman ultradifferentiable C₀-semigroups - Markin, M.V. (Український математичний журнал, 2008)
Necessary and sufficient conditions for a scalar-type spectral operator in a Banach space to be a generator of a Carleman ultradifferentiable C₀-semigroup are found. The conditions are formulated exclusively in terms of the spectrum of the operator. Знайдено необхідні та достатні умови для того, щоб спектральний оператор скалярного типу в банаховому просторі породжував ультрадиференційовну C₀-напівгрупу Карлемана. Ці умови сформульовано виключно у термінах спектра оператора.